Mechanisms and Drug Therapies of Bioprosthetic Heart Valve Calcification - Wen, Shuyu; Zhou, Ying; Yim, Wai Yen; Wang, Shijie; Xu, Li; Shi, Jiawei; Qiao, Weihua; Dong, Nianguo (Frontiers in Pharmacology, 2022)
Valve replacement is the main therapy for valvular heart disease, in which a diseased valve is replaced by mechanical heart valve (MHV) or bioprosthetic heart valve (BHV). Since the 2000s, BHV surpassed MHV as the leading option of prosthetic valve substitute because of its excellent hemocompatible and hemodynamic properties. However, BHV is apt to structural valve degeneration (SVD), resulting in limited durability. Calcification is the most frequent presentation and the core pathophysiological process of SVD. Understanding the basic mechanisms of BHV calcification is an essential prerequisite to address the limited-durability issues. In this narrative review, we provide a comprehensive summary about the mechanisms of BHV calcification on 1) composition and site of calcifications; 2) material-associated mechanisms; 3) host-associated mechanisms, including immune response and foreign body reaction, oxidative stress, metabolic disorder, and thrombosis. Strategies that target these mechanisms may be explored for novel drug therapy to prevent or delay BHV calcification.